The Influence Of Customer Perspectives Related To Business Ethics On Customer Loyalty In The Shopee Market Place (International Journal of Educational Technology Research, 2024)
This study aims to determine the effect of a customer perspective on business ethics on customer loyalty in the Shopeemarketplace. The results of the study show that having a good customer perspective will lead to increased customer loyalty to the Shopee Marketplace itself. This study uses qualitative research methods with data collection techniques through observation and questionnaires.